Eliminating HIV transmission through breast milk from women taking antiretroviral drugs - (:unkn) unknown (My University, 2021)
Ameena Goga and colleagues argue that frequent testing of maternal viral load is needed to eliminate HIV transmission through breast milk in low and middle income settings
Keywords: African Research